2021
DOI: 10.3389/fcomp.2021.713719
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Review of the 2018–2020 SHL Challenge on Transportation and Locomotion Mode Recognition From Mobile Sensors

Abstract: The Sussex-Huawei Locomotion-Transportation (SHL) Recognition Challenges aim to advance and capture the state-of-the-art in locomotion and transportation mode recognition from smartphone motion (inertial) sensors. The goal of this series of machine learning and data science challenges was to recognize eight locomotion and transportation activities (Still, Walk, Run, Bus, Car, Train, Subway). The three challenges focused on time-independent (SHL 2018), position-independent (SHL 2019) and user-independent (SHL 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Some of the best results posted during the challenges were achieved using the MultiResNet architecture [ 5 ], IndRNN architecture [ 17 ] and the DenseNetX architecture [ 18 ]. Nevertheless, these challenges have also shown that, alhough classical machine learning pipelines require domain knowledge for meaningful feature extraction, selection and tuning [ 19 ], they are still very competitive and sometimes produce better results than the aforementioned deep learning methods. An additional advantage is that they can be more easily understood and adapted to the specifics of new activity recognition scenarios, which is why they are the chosen approach in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the best results posted during the challenges were achieved using the MultiResNet architecture [ 5 ], IndRNN architecture [ 17 ] and the DenseNetX architecture [ 18 ]. Nevertheless, these challenges have also shown that, alhough classical machine learning pipelines require domain knowledge for meaningful feature extraction, selection and tuning [ 19 ], they are still very competitive and sometimes produce better results than the aforementioned deep learning methods. An additional advantage is that they can be more easily understood and adapted to the specifics of new activity recognition scenarios, which is why they are the chosen approach in this paper.…”
Section: Related Workmentioning
confidence: 99%